Run Time and Perceived Performance Influenced by External Feedback in Endurance Athletes - Jancik, Allison M.; Vang, Joua; Kiekhoefer, Laura D.; Lose, Sarah R. (My University, 2013)
Research on the impact of frequency of encouragement for run training has never been explored. To give insight into coaching methods for practices and competitions, knowing how much to encourage athletes is important. The purpose of this study was to gain insight into which amount of encouragement provides the most influence on running performance during training sessions for endurance runners.
Color poster with text and tables.
Keywords: Endurance runners; Encouragement--Influence of; Posters